PENGARUH PENGELOLAAN KELAS DAN KOMPETENSI KEPRIBADIAN GURU TERHADAP PERUBAHAN PERILAKU SISWAKELAS VIIIPADA PELAJARAN PAI DI SMP NEGERI 4 SELONG - Mahyudin Mahyudin; Ahmad Sulhan; Al Kusaeri (Nusantara Hasana Journal, 2021)
This study aims to 1) explain the effect of classroom management on changes in student behavior, 2) explain the influence of teacher personality competence on changes in student behavior, 3) explain the effect of classroom management and the influence of teacher personality competence on changes in student behavior in Islamic Education subjects at Junior High School 4 Selong. This study uses a quantitative approach where the data used are primary data obtained through a questionnaire/questionnaire. The research method used is descriptive analysis, simple regression analysis, and multiple regression analysis. The results of this study indicate that: 1) classroom management (X1) significantly influences changes in student behavior (Y) in Islamic Education subjects at Junior High School 4 Selong with a correlation value of 0.564; 2) The teacher's personality competence (X2) significantly influences changes in student behavior (Y) in Islamic Education subjects at Junior High School 4 Selong with a correlation value of 0.612; 3) Class management (X1) and teacher personality competence (X2) has a significant effect on changes in student behavior (Y) in Islamic Education subjects at Junior High School 4 Selong by 50.7% with a  correlation value of 0.712.